Modelo de integração das questões sociais no desenvolvimento de megaprojetos no setor de mineração: um caminho para a construção da licença social para operar - Juliana Machado de Vilhena (2019)
In the past years, society is been increasingly aware and concerned about the social, environmental and development performance of the mining industry. Due to higher perception of risks involving extractive activities and social and environmental impacts it brings, social conflicts are arising within the comunities affected by these activities and as a consequence they are demanding to be involved on decision making process with regards to benefits mining companies should offer as a way to offset these impacts. Thus, social issues become increasingly strategic on decision making process of Mining Companies, forcing them to work on the concept of social license to operate. Respecting such context, this research intends to analyze socio-environmental transformations and social impacts in the mining territories and intends also to propose a Model that will incorporate social issues within the mining management projects, estimulating a previous social participation before implementating a new venture.Through the methodological approach of Design Science Research (DSR), the research seeks to establish a link between theory and practice. The Model proposes guidelines to be applied throughout the typical life cycle of a mining innvestment, especially for the development phases (FEL 1, FEL 2 and FEL 3), pointing out how to incorporate the results of the Social Impact Assessment (SIA) as well as perceptions and recommendations of potentially affected communities within each of the phases of the project. Outcomes of this research reinforce literature studies, pointing out the dynamic interaction between risks to local communities and the risks to business, the necessity to initiate the participatory process since the early stages, the importance of SIA to reduce adverse impacts and maximize benefits, generating shared value by improving outcomes for local communities and businesses. This model has been validated by specialists who considered it feasible to be implemented on mining companies Project Management. However, it was widely emphasized the need of changing culture and mindset of Mining Companies to insert such social participation since the very beginning stages of the development of Project Management.